Copper sub-nanocluster-metal organic framework composite catalyst as well as preparation method and application thereof
By forming a composite catalyst of copper subnano clusters on the metal organic frame substrate, the problem of low methane selectivity in carbon dioxide reduction is solved, and the efficient carbon dioxide reduction methane preparation reaction is achieved, which improves Faraday efficiency and yield .
Patent Information
- Application Number
- CN202411463392.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-10
AI Technical Summary
In the prior art, copper catalysts have low selectivity due to carbon-carbon coupling during carbon dioxide reduction and are difficult to achieve efficient conversion.
Using copper sub-nano cluster-metal organic frame composite catalyst, the copper sub-nano cluster is formed on the metal organic frame substrate with a porous structure, and the catalyst is prepared by impregnation method and in-situ electroreduction reaction for electrocatalytic carbon dioxide reduction. Prepare methane.
High Faraday efficiency and yield are achieved, and the selectivity of carbon dioxide reduction to methane is improved.
Smart Images

Figure CN119287443A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a copper sub-nano cluster-metal organic framework composite catalyst, a preparation method and application thereof. Background Art
[0002] The direct emission of carbon dioxide tail gas from the combustion of large amounts of fossil fuels into the atmosphere has caused a series of global environmental problems. At the same time, the increasing reduction of fossil resources has also caused people to worry about energy issues. The electroreduction of carbon dioxide into methane can not only alleviate the environmental pressure caused by the direct emission of excessive carbon dioxide into the atmosphere, but also obtain fuel with high energy density. It is a green and sustainable conversion method with practical significance.
[0003] Copper metal has shown good ability to stabilize the key intermediate *CHO in the reduction of carbon dioxide to methane, but it faces the problem of low methane selectivity due to the easy occurrence of carbon-carbon coupling on the copper surface. Therefore, the development of a new and efficient catalyst is of great significance to improve the selectivity of carbon dioxide electroreduction to methane. Summary of the invention
[0004] In view of this, the technical problem to be solved by the present invention is to provide a copper sub-nano cluster-metal organic framework composite catalyst, a preparation method and application thereof, and the copper sub-nano cluster-metal organic framework composite catalyst is applied to the reaction of electrocatalytic carbon dioxide reduction to prepare methane, which can achieve higher Faraday efficiency and yield.
[0005] The present invention provides a copper sub-nano cluster-metal organic framework composite catalyst, comprising:
[0006] Substrate; the substrate is a metal organic framework with a porous structure;
[0007] Copper sub-nanoclusters are formed on the substrate.
[0008] Preferably, the metal organic framework is UIO-66-NDC or UIO-66.
[0009] Preferably, the mass content of copper element in the copper sub-nano cluster-metal organic framework composite catalyst is 2% to 5%.
[0010] The present invention also provides a method for preparing the copper sub-nano cluster-metal organic framework composite catalyst described above, comprising the following steps:
[0011] A) mixing a copper salt solution with metal organic framework powder, dispersing by ultrasonication, impregnating and reacting, and drying to obtain a catalyst precursor;
[0012] B) subjecting the catalyst precursor to an in-situ electro-reduction reaction to obtain a copper sub-nano cluster-metal organic framework composite catalyst.
[0013] Preferably, in step A), the copper salt in the copper salt solution is copper nitrate, and the solvent is acetonitrile;
[0014] The copper salt solution is obtained by dissolving an anhydrous compound of copper salt or a crystalline hydrate of copper salt in acetonitrile; the crystalline hydrate of copper salt is copper nitrate trihydrate; the dosage ratio of copper nitrate trihydrate to acetonitrile is 140-145 mg:2 mL.
[0015] Preferably, in step A), the mass ratio of the crystalline hydrate of the copper salt to the metal organic framework powder is 140-145:70-100.
[0016] Preferably, in step A), the impregnation reaction is carried out under stirring;
[0017] The impregnation reaction is carried out at room temperature for 10 to 14 hours;
[0018] After the impregnation reaction, the method further comprises: centrifugal separation, washing with ethanol, and centrifugal separation again.
[0019] Preferably, step B) comprises:
[0020] B1) dispersing the catalyst precursor in ethanol, ultrasonicating, adding Nafion isopropanol aqueous solution, ultrasonicating again, spraying the obtained dispersion on the surface of the gas diffusion electrode, and drying to obtain a working electrode;
[0021] B2) using carbon dioxide as the reaction raw material gas and carrier gas, using the working electrode, a platinum wire as the counter electrode, a silver / silver chloride electrode as the reference electrode, and a potassium hydroxide aqueous solution as the electrolyte, assembling an electrolytic cell, applying a potential and performing an in-situ electroreduction reaction to obtain a copper sub-nano cluster-metal organic framework composite catalyst.
[0022] The present invention also provides an application of the copper sub-nano cluster-metal organic framework composite catalyst described above, or the copper sub-nano cluster-metal organic framework composite catalyst prepared by the preparation method described above in the electrocatalytic reduction of carbon dioxide to produce methane.
[0023] The present invention provides a copper sub-nano cluster-metal organic framework composite catalyst, comprising: a substrate; the substrate is a metal organic framework with a porous structure; and copper sub-nano clusters formed on the substrate. Compared with the prior art, the present invention uses the metal organic framework as a substrate, obtains a copper sub-nano cluster catalyst confined in the organic framework by an impregnation method and an in-situ electro-reduction reaction, and uses the catalyst to electrocatalyze carbon dioxide reduction to produce methane, achieving a higher Faraday efficiency and yield. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scanning electron microscope image of the copper sub-nano cluster-metal organic framework composite catalyst precursor of Example 1 of the present invention;
[0025] Figure 2 This is a scanning electron elemental imaging image of the copper sub-nano cluster-metal organic framework composite catalyst precursor of Example 1 of the present invention;
[0026] Figure 3 This is an in-situ X-ray absorption near-edge structure spectrum of the copper sub-nano cluster-metal organic framework composite catalyst of Example 3 of the present invention;
[0027] Figure 4 This is an in-situ extended edge X-ray absorption fine structure spectrum of the copper sub-nano cluster-metal organic framework composite catalyst of Example 3 of the present invention;
[0028] Figure 5 is a Faraday efficiency diagram of the copper sub-nano cluster-metal organic framework composite catalyst generating methane at different set potentials in Example 3 of the present invention;
[0029] Figure 6 This is a partial current density variation trend diagram of the copper sub-nano cluster-metal organic framework composite catalyst generating methane at different set potentials in Example 3 of the present invention. DETAILED DESCRIPTION
[0030] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The present invention provides a copper sub-nano cluster-metal organic framework composite catalyst, comprising:
[0032] Substrate; the substrate is a metal organic framework with a porous structure;
[0033] Copper sub-nanoclusters are formed on the substrate.
[0034] In the present invention, the metal organic framework with a porous structure provides loading sites for copper sub-nanoclusters.
[0035] Preferably, the mass content of copper in the copper sub-nano cluster-metal organic framework composite catalyst is 2% to 5%, such as 2.35%. The copper in the copper sub-nano cluster-metal organic framework composite catalyst is evenly distributed.
[0036] In certain embodiments of the present invention, the metal organic framework is UIO-66-NDC or UIO-66. Specifically, UIO-66-NDC is formed by the coordination of zirconium ions and 1,4-naphthalene dicarboxylic acid; UIO-66 is formed by the coordination of zirconium ions and 1,4-phthalic acid.
[0037] In certain embodiments of the present invention, the diameter of the copper sub-nano cluster is 0.4-0.8 nm, such as 0.7 nm.
[0038] The present invention also provides a method for preparing the copper sub-nano cluster-metal organic framework composite catalyst described above, comprising the following steps:
[0039] A) mixing a copper salt solution with metal organic framework powder, dispersing by ultrasonication, impregnating and reacting, and drying to obtain a catalyst precursor;
[0040] B) subjecting the catalyst precursor to an in-situ electro-reduction reaction to obtain a copper sub-nano cluster-metal organic framework composite catalyst.
[0041] Regarding step A):
[0042] The copper salt in the copper salt solution is copper nitrate, and the solvent is acetonitrile. The copper salt solution can be obtained by dissolving an anhydrous compound of the copper salt or a crystalline hydrate of the copper salt in acetonitrile; the crystalline hydrate of the copper salt can be copper nitrate trihydrate; the usage ratio of the copper nitrate trihydrate to acetonitrile is 140-145 mg:2 mL, such as 142.2 mg:2 mL.
[0043] The metal organic framework powder is UIO-66-NDC powder or UIO-66 powder. The metal organic framework powder can be synthesized by a solvothermal method.
[0044] In certain embodiments of the present invention, the method for preparing the UIO-66-NDC powder comprises the following steps:
[0045] A zirconium source, 1,4-naphthalene dicarboxylic acid, acetic acid and N,N-dimethylformamide are mixed and reacted to obtain UIO-66-NDC powder.
[0046] The zirconium source is ZrCl4.
[0047] The usage ratio of the zirconium source, 1,4-naphthalene dicarboxylic acid, acetic acid and N,N-dimethylformamide is 132-133 mg: 124-126 mg: 3-5 mL: 24-26 mL; for example, 132.5 mg: 125.0 mg: 4.0 mL: 25.0 mL.
[0048] The reaction temperature is 110-130° C., such as 120° C., and the reaction time is 22-26 h, such as 24 h.
[0049] After the reaction, the method further includes: solid-liquid separation. The method of solid-liquid separation is vacuum filtration. After the solid-liquid separation, the method further includes: cleaning and drying. The cleaning agent is acetone. The drying temperature is 55 to 65° C., such as 60° C.; the drying time is 8 to 16 hours, such as 12 hours.
[0050] In certain embodiments of the present invention, the method for preparing the UIO-66 powder comprises the following steps:
[0051] A zirconium source, 1,4-phthalic acid, acetic acid and N,N-dimethylformamide are mixed and reacted to obtain UIO-66-NDC powder.
[0052] The zirconium source is ZrCl4.
[0053] The usage ratio of the zirconium source, 1,4-phthalic acid, acetic acid and N,N-dimethylformamide is 211-213 mg: 135-137 mg: 3-5 mL: 23-25 mL; for example, 212 mg: 136.0 mg: 4.0 mL: 24.0 mL.
[0054] The reaction temperature is 110-130° C., such as 120° C., and the reaction time is 22-26 h, such as 24 h.
[0055] After the reaction, the method further includes: solid-liquid separation. The method of solid-liquid separation is vacuum filtration. After the solid-liquid separation, the method further includes: cleaning and drying. The cleaning agent is acetone. The drying temperature is 55 to 65° C., such as 60° C.; the drying time is 8 to 16 hours, such as 12 hours.
[0056] The mass ratio of the crystalline hydrate of the copper salt to the metal organic framework powder is 140-145:70-100, such as 142.2:100.
[0057] The impregnation reaction is carried out under stirring conditions. The stirring speed is 450-550 rpm, such as 500 rpm. The stirring is carried out by magnetic stirring.
[0058] The impregnation reaction is carried out at room temperature for 10 to 14 hours, such as 12 hours.
[0059] After the impregnation reaction, the method further comprises:
[0060] The mixture was centrifuged, washed with ethanol to remove copper nitrate adsorbed on the surface, and then centrifuged again.
[0061] The drying may be vacuum drying at room temperature.
[0062] Regarding step B):
[0063] The catalyst precursor is subjected to an in-situ electric reduction reaction to obtain a copper sub-nano cluster-metal organic framework composite catalyst.
[0064] In certain embodiments of the present invention, step B) comprises:
[0065] B1) dispersing the catalyst precursor in ethanol, adding a perfluorosulfonic acid-polytetrafluoroethylene copolymer isopropanol aqueous solution (Nafion isopropanol aqueous solution) after ultrasonication, and spraying the obtained dispersion on the surface of the gas diffusion electrode after ultrasonication. After drying, a working electrode is obtained;
[0066] B2) using carbon dioxide as the reaction raw material gas and carrier gas, adopting the working electrode, using a platinum wire as a counter electrode, using a silver / silver chloride electrode as a reference electrode, and using a potassium hydroxide aqueous solution as an electrolyte, assembling an electrolytic cell, and applying a potential to perform an in-situ electroreduction reaction to obtain a copper sub-nano cluster-metal organic framework composite catalyst.
[0067] Regarding step B1):
[0068] The usage ratio of the catalyst precursor to ethanol is 8-10 mg: 2-4 mL; for example, 9 mg: 3 mL.
[0069] The catalyst precursor is dispersed in ethanol and ultrasonicated for 1.5 to 2.5 minutes, for example, 2 minutes.
[0070] The mass concentration of the Nafion isopropanol aqueous solution is 4% to 6%, such as 5%.
[0071] The time for the second ultrasound is 4.5 to 5.5 minutes, for example, 5 minutes.
[0072] The surface area of the gas diffusion electrode is 3×6 cm 2 .
[0073] In the working electrode, the loading amount of the catalyst precursor is 0.4-0.6 mg / cm 2 , for example 0.5mg / cm 2 .
[0074] Regarding step B2):
[0075] The ion exchange membrane in the electrolytic cell is a Nafion 117 membrane.
[0076] The electrolyte in the electrolytic cell is a 1 mol / L potassium hydroxide aqueous solution, and the flow rate of the electrolyte is controlled to be 18-22 mL / min; for example, 20 mL / min.
[0077] The gas flow rate of the carbon dioxide is 18-22 mL / min, for example 20 mL / min.
[0078] The in situ electroreduction reaction is carried out in a potential range of +0.42 V to -1.98 V relative to a standard hydrogen electrode.
[0079] After an in-situ electroreduction reaction, a copper sub-nano cluster-metal organic framework composite catalyst is obtained on the surface of the working electrode.
[0080] The preparation method of the copper sub-nano cluster-metal organic framework composite catalyst provided by the invention is simple, easy to synthesize in large quantities and low in cost.
[0081] The present invention also provides an application of the copper sub-nano cluster-metal organic framework composite catalyst described above, or the copper sub-nano cluster-metal organic framework composite catalyst prepared by the preparation method described above, in the electrocatalytic reduction of carbon dioxide to produce methane. Specifically, it is an application as a catalyst for the electrocatalytic reduction of carbon dioxide to produce methane.
[0082] The present invention successfully realizes the chemical reaction of electrocatalytic reduction of carbon dioxide to obtain methane by introducing a copper sub-nano cluster-metal organic framework composite catalyst with a specific structure, and has a high Faraday efficiency and yield.
[0083] In the method of electrocatalytic reduction of carbon dioxide to obtain methane, the working electrode loaded with the copper sub-nano cluster-metal organic framework composite catalyst can be directly used, or the electrolytic cell of the copper sub-nano cluster-metal organic framework composite catalyst can be directly prepared.
[0084] The present invention has no particular limitation on the sources of the raw materials used above, and they can be generally commercially available.
[0085] In order to further illustrate the present invention, a copper sub-nano cluster-metal organic framework composite catalyst, its preparation method and application provided by the present invention are described in detail below in combination with examples, but it should not be understood as limiting the scope of protection of the present invention.
[0086] In the embodiment:
[0087] Preparation of UIO-66-NDC powder:
[0088] 132.5 mg ZrCl4, 125.0 mg 1,4-naphthalenedicarboxylic acid, 4.0 mL acetic acid, and 25.0 mL N,N-dimethylformamide were mixed in a 50.0 mL polytetrafluoroethylene reactor, and then the reactor was transferred to an oven and reacted at 120°C for 24 h. The reaction mixture was separated by vacuum filtration, and the obtained powder was washed with acetone and dried in an oven at 60°C to obtain UIO-66-NDC powder.
[0089] Preparation of UIO-66 powder:
[0090] 212.0 mg ZrCl4, 136.0 mg 1,4-phthalic acid, 4.0 mL acetic acid, and 24.0 mL N,N-dimethylformamide were mixed in a 50.0 mL polytetrafluoroethylene reactor, and then the reactor was transferred to an oven and reacted at 120°C for 24 h. The mixture was separated by vacuum filtration, and the obtained powder was washed with acetone and dried in an oven at 60°C to obtain UIO-66 powder.
[0091] Example 1
[0092] Preparation of copper sub-nano cluster-metal organic framework composite catalyst precursor:
[0093] 142.2 mg Cu(NO3)2·3H2O was dissolved in 2 mL acetonitrile, and 100 mg UIO-66-NDC was added. After ultrasonic dispersion, the mixture was reacted for 12 h under magnetic stirring (stirring speed was 500 rpm) at room temperature, and then centrifuged. The copper nitrate adsorbed on the surface of UIO-66-NDC was washed away with ethanol, and then centrifuged and dried in vacuum at room temperature to obtain a copper sub-nano cluster-metal organic framework composite catalyst precursor.
[0094] The copper sub-nano cluster-metal organic framework composite catalyst precursor obtained in Example 1 was analyzed using a scanning electron microscope, and its scanning electron microscope image was obtained as shown in Figure 1 , scanning electron element imaging diagram see Figure 2 .
[0095] Figure 1 This is a scanning electron microscope image of the copper sub-nano cluster-metal organic framework composite catalyst precursor of Example 1 of the present invention. The obtained copper sub-nano cluster-metal organic framework catalyst precursor has an octahedral morphology and a particle size of 300-400 nm.
[0096] Figure 2 This is a scanning electron elemental imaging image of the copper sub-nano cluster-metal organic framework composite catalyst precursor of Example 1 of the present invention. It can be seen that the copper element is uniformly distributed in the copper sub-nano cluster-metal organic framework composite catalyst precursor.
[0097] Example 2
[0098] 9 mg of the copper sub-nano cluster-metal organic framework composite catalyst precursor prepared in Example 1 was dispersed in 3 mL of ethanol, ultrasonicated for 2 min, and then 45 μL of 5 wt% Nafion isopropanol aqueous solution was added and ultrasonicated for 5 min. The dispersion was sprayed on a 3×6 cm 2 The surface of the gas diffusion electrode is used to obtain a working electrode. The catalyst loading in the working electrode is 0.5 mg / cm 2 .
[0099] Example 3
[0100] Preparation of copper sub-nano cluster-metal organic framework composite catalyst:
[0101] In the flow electrolysis cell, Nafion 117 membrane was used as the ion exchange membrane, the working electrode, platinum wire and silver / silver chloride electrode obtained in Example 2 were used as the working electrode, counter electrode and reference electrode respectively, the electrolyte was 1 mol / L potassium hydroxide aqueous solution, and the solution flow rate was controlled by a peristaltic pump at 20 mL / min. Carbon dioxide with a purity of 99.999% was used as the reaction raw gas and carrier gas, and the gas flow rate was 20 mL / min.
[0102] Two linear sweep voltammetry tests (i.e., in-situ electroreduction reactions) were performed in the potential range of +0.42 V to -1.98 V relative to a standard hydrogen electrode to obtain a copper subnano cluster-metal organic framework composite catalyst.
[0103] The mass content of copper element in the copper sub-nano cluster-metal organic framework composite catalyst is 2.35%.
[0104] The copper sub-nano cluster-metal organic framework composite catalyst obtained in Example 3 was analyzed by X-ray absorption fine structure spectroscopy, and its in-situ X-ray absorption near-edge structure spectrum was obtained. Figure 3 , in situ extended X-ray absorption fine structure spectroscopy Figure 4 .
[0105] Figure 3 This is an in-situ X-ray absorption near-edge structure spectrum of the copper sub-nano cluster-metal organic framework composite catalyst of Example 3 of the present invention. Figure 4 This is an in-situ extended edge X-ray absorption fine structure spectrum of the copper sub-nano cluster-metal organic framework composite catalyst of Example 3 of the present invention. Figure 3 and Figure 4 It is proved that under the condition of applied potential, copper exists in the form of sub-nanoclusters, and the diameter of the copper sub-nanoclusters is 0.7nm.
[0106] Example 4
[0107] Product selectivity testing of copper subnanocluster-metal organic framework composite catalysts in electrocatalytic carbon dioxide reduction.
[0108] Under the reaction conditions of Example 3, a constant potential test was adopted. The potential was set to -1.7V (relative to the standard hydrogen electrode), and the constant potential test was performed for 1200s. During the reaction, carbon dioxide was used as the carrier gas, and the carbon dioxide flow rate was set to 20mL / min. The gaseous product was blown out and blown into the gas chromatograph for online detection of the gas composition. The oxygen produced at the anode during the reaction was discharged into the air. After the reaction was completed, the liquid product was detected by hydrogen nuclear magnetic resonance spectroscopy. After the test was completed, the total potential was set to -2.0V, -2.3V, -2.6V, -2.9V, and -3.2V (all relative to the standard hydrogen electrode) in sequence, and other conditions were kept unchanged for testing. The Faraday efficiency of the electrocatalytic reduction of carbon dioxide to prepare methane by copper subnano cluster-metal organic framework composite catalyst is shown in Figure 5 , the partial current density of methane is Figure 6 .
[0109] Figure 5 This is a Faraday efficiency diagram of the copper sub-nano cluster-metal organic framework composite catalyst generating methane at different set potentials in Example 4 of the present invention. In the potential range of -1.7 to -3.2 V relative to the standard hydrogen electrode, the Faraday efficiency of the copper sub-nano cluster-metal organic catalyst for methane is greater than 58.0%. When the potential is -2.6 V, the Faraday efficiency of methane is the highest, which is 72.0%.
[0110] Figure 6 This is a partial current density variation trend diagram of methane generated by the copper sub-nano cluster-metal organic framework composite catalyst in Example 4 of the present invention at different set potentials. In the potential range of -1.7 to -3.2 V relative to the standard hydrogen electrode, the partial current density of methane increases as the potential becomes negative. When the potential is -3.2 V, the partial current density of methane is the largest, which is -361.0 mA cm -2 .
[0111] Example 5
[0112] The difference from Example 1 is:
[0113] Substituting UIO-66-NDC with UIO-66, a copper sub-nano cluster-metal organic framework composite catalyst precursor was prepared;
[0114] The copper sub-nano cluster-metal organic framework composite catalyst precursor is used to prepare a working electrode according to the method of Example 2;
[0115] The working electrode is used to prepare a copper sub-nano cluster-metal organic framework composite catalyst according to the method of Example 3;
[0116] The copper sub-nano cluster-metal organic framework composite catalyst was tested according to the method of Example 4. In the potential range of -1.7 to -3.2 V relative to the standard hydrogen electrode, the Faradaic efficiency of the copper sub-nano cluster-metal organic framework composite catalyst for electrocatalytic reduction of carbon dioxide to prepare methane was greater than 50%. When the potential was -2.9 V, the Faradaic efficiency of methane was the highest, which was 62.0%. The partial current density of methane increased as the potential became negative. When the potential was -2.9 V, the partial current density of methane was the largest, which was -328.7 mA cm -2 .
[0117] The description of the above embodiments is only used to help understand the method of the present invention and its core idea. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features disclosed herein.
Claims
1. A copper sub-nano cluster-metal organic framework composite catalyst, comprising: Substrate; the substrate is a metal organic framework with a porous structure; Copper sub-nanoclusters are formed on the substrate.
2. The copper sub-nano cluster-metal organic framework composite catalyst according to claim 1, characterized in that: The metal organic framework is UIO-66-NDC or UIO-66.
3. The copper sub-nano cluster-metal organic framework composite catalyst according to claim 1, characterized in that: In the copper sub-nano cluster-metal organic framework composite catalyst, the mass content of copper element is 2% to 5%.
4. A method for preparing the copper sub-nano cluster-metal organic framework composite catalyst according to any one of claims 1 to 3, comprising the following steps: A) mixing a copper salt solution with metal organic framework powder, dispersing by ultrasonication, impregnating and reacting, and drying to obtain a catalyst precursor; B) subjecting the catalyst precursor to an in-situ electro-reduction reaction to obtain a copper sub-nano cluster-metal organic framework composite catalyst.
5. The preparation method according to claim 4, characterized in that: In step A), the copper salt in the copper salt solution is copper nitrate, and the solvent is acetonitrile; The copper salt solution is obtained by dissolving an anhydrous compound of copper salt or a crystalline hydrate of copper salt in acetonitrile; the crystalline hydrate of copper salt is copper nitrate trihydrate; the dosage ratio of copper nitrate trihydrate to acetonitrile is 140-145 mg:2 mL.
6. The preparation method according to claim 4, characterized in that: In step A), the mass ratio of the crystalline hydrate of the copper salt to the metal organic framework powder is 140-145:70-100.
7. The preparation method according to claim 4, characterized in that: In step A), the impregnation reaction is carried out under stirring; The impregnation reaction is carried out at room temperature for 10 to 14 hours; After the impregnation reaction, the method further comprises: centrifugal separation, washing with ethanol, and centrifugal separation again.
8. The preparation method according to claim 4, characterized in that: Step B) comprises: B1) dispersing the catalyst precursor in ethanol, ultrasonicating, adding Nafion isopropanol aqueous solution, ultrasonicating again, spraying the obtained dispersion on the surface of the gas diffusion electrode, and drying to obtain a working electrode; B2) using carbon dioxide as the reaction raw material gas and carrier gas, adopting the working electrode, using a platinum wire as a counter electrode, using a silver / silver chloride electrode as a reference electrode, and using a potassium hydroxide aqueous solution as an electrolyte, assembling an electrolytic cell, and applying a potential to perform an in-situ electroreduction reaction to obtain a copper sub-nano cluster-metal organic framework composite catalyst.
9. Use of the copper sub-nano cluster-metal organic framework composite catalyst according to any one of claims 1 to 3, or the copper sub-nano cluster-metal organic framework composite catalyst prepared by the preparation method according to any one of claims 4 to 8 in the electrocatalytic reduction of carbon dioxide to produce methane.
Citation Information
Cited By
UiO-66 (at) Cu2O composite electrocatalyst, gas diffusion electrode and preparation method and application of UiO-66 (at) Cu2O composite electrocatalyst
CN120138719A